2006
DOI: 10.1016/j.ejor.2005.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Finding the K best policies in a finite-horizon Markov decision process

Abstract: Directed hypergraphs represent a general modelling and algorithmic tool, which have been successfully used in many different research areas such as artificial intelligence, database systems, fuzzy systems, propositional logic and transportation networks. However, modelling Markov decision processes using directed hypergraphs has not yet been considered.In this paper we consider finite-horizon Markov decision processes (MDPs) with finite state and action space and present an algorithm for finding the K best det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…A very similar problem has been explored by Nielsen et al [10][11][12]. Nielsen and Kristensen observed that the problem of finding optimal history-dependent policies (maps from the state space crossed with the time step to the action space) can be modeled as finding "a minimum weight hyperpath" in directed hypergraphs.…”
Section: Introductionmentioning
confidence: 93%
“…A very similar problem has been explored by Nielsen et al [10][11][12]. Nielsen and Kristensen observed that the problem of finding optimal history-dependent policies (maps from the state space crossed with the time step to the action space) can be modeled as finding "a minimum weight hyperpath" in directed hypergraphs.…”
Section: Introductionmentioning
confidence: 93%
“…Nielsen and Kristensen [14] created a system that modeled Markov decision processes using directed hypergraphs in order to find the K best policies in a finite-horizon. The system ranked the first K deterministic Markov policies in non-decreasing order using an additive criterion of optimality.…”
Section: Symmetry 2019 11 X For Peer Review 3 Of 18mentioning
confidence: 99%
“…It can be seen that the higher the value of N prev the larger the number of integrals in equations (15), (17), and (21). This leads to difficulties in obtaining results.…”
Section: Expression Of F T F (T) With T 6 Tmentioning
confidence: 99%